Analisa Manajemen Risiko pada UMKM Di Sektor Kreatif Menggunakan Framework ISO 31000 dan Matriks Risiko: Studi Kasus Fresco Florist di Kota Bandung - Hesti Hisani Latifah Hamdah; Anisa Roshy Rosdian; Aghnia Yasyfa; Almaira Sarah Junjunan; Alfiana Alfiana (Ekopedia: Jurnal Ilmiah Ekonomi, 2026)
Fresco Florist is one of the micro, small, and medium enterprises (MSMEs) located in Bandung, founded by Adhela Nuzul Fariqa in 2022. This business operates in the floral arrangement sector with the concept of an “affordable aesthetic florist” that emphasizes unique designs, visual appeal, and affordable prices. Since its establishment, Fresco Florist has served various customer needs for special occasions such as graduations, birthdays, and engagements, and has gained recognition through active promotion on social media platforms. The essence of this study is to identify the sources of risk faced by Fresco Florist and to analyze the causes and mitigation strategies implemented to overcome these risks. This research employs a qualitative descriptive analysis method, with risk identification conducted using the risk matrix and SWOT analysis approaches. The results show that Fresco Florist encounters several categories of risks, including operational, financial, marketing, market, human resources (HR), and legal risks. Through the implementation of mitigation strategies such as supplier diversification, a pre-order system, and digital marketing enhancement, Fresco Florist has been able to maintain its business stability and competitiveness within Bandung’s florist industry..